Perancangan Sistem Informasi Customer Relationship Management Dengan Segmentasi Pelanggan Berbasis Laravel - Ovan Kurniawan; Mulyati (PPPM Institut Teknologi Pagar Alam, 2026)
PT Cemerlang Sejahtera Semesta is a building materials distributor in Palembang that serves more than 300 partner stores or customers with a high daily transaction volume. Based on the results of an analysis using the PIECES method the current business processes exhibit weaknesses in ordering time efficiency and credit limit management, thereby creating the risk of non-payment and a lack of appreciation for loyal partners. This study aims to design a web-based Customer Relationship Management (CRM) information system using the Laravel framework and a MySQL database. The development method used is the Rational Unified Process (RUP) with model design through Use Case, Activity, and Entity Relationship Diagrams (ERD). The resulting system integrates self-service ordering features, digital receipt recording, shipment tracking, credit limit automation, and membership segmentation (Gold, Silver, Bronze) accompanied by reward points. System testing using the Black Box Testing method demonstrated that the application achieved a valid success rate across all key module functionalities. This CRM implementation is expected address previous operational challenges, minimize uncollectible receivables, and strengthen long-term partner loyalty.